Bo and the dragon-pup - Elliott, Rebecca (2020)
Rainbow Tinseltail (called Bo) has never actually seen a dragon, but when things start going missing from Sparklegrove School for Unicorns all clues seem to point to a dragon pup called Scorch--but when Scorch does not return to the dragon caves, Bo and her friends become worried that he has gotten lost in the forest and they set out to find their new friend.
Keywords: Unicorns -- Juvenile fiction; Dragons -- Juvenile fiction; Magic -- Juvenile fiction; Friendship -- Juvenile fiction; Diaries -- Juvenile fiction; Unicorns -- Fiction; Dragons -- Fiction; Magic -- Fiction; Friendship -- Fiction; Diaries -- Fiction; Diary fiction